Shirley Geok-Lin Lim’s Fiction: A Post-Colonial Hybrid Literature - See, Tho Siew Hiang (2003)
This research seeks to examine the nationalistic and hybrid elements that permeate Shirley Geok-Lin Lim’s fiction: three collections of short stories and a novel, Joss and Gold. They portray various elements which cumulated to a nationalistic voice and which depict relationships of the peoples of a multi-cultural, multi-religious and multi-racial nation. Lim’s stories represent a vast repertoire of themes of a struggling and fledgling nation and her peoples, while her novel represents an observation of and desire for a united, tolerant and cosmopolitan Malaysia with a fusion and acceptance of all the races, cultures and religions. Much has been said and researched on about her works, especially her extensive collection of poems. Thus, this research aims to look at a different angle of her works - her fiction, which includes her first novel that took a few decades to be completed, and which also span decades.